Optimization of Postprocessing parameters for abdominal Forensic CT scans - Pernille Lund Hansen; Peter Mygind Leth; Pernille Aagaard Nielsen; Dina Maria Bech; Julie Brandhøj Nielsen; Svea Deppe Mørup; Anette Koch Holst; Lene Bak; Mette R. Poulsen; Pernille W. Greisen; Dennis Lund Hansen; Helle Precht (Forensic Science International: Synergy, 2024)
Aim: Postmortem Computed Tomography (PMCT) is gradually introduced at forensic institutes. Image reconstruction software can increase diagnostic potential in CT by increasing distinction between structures and reduction of artifacts. The aim of this study was to develop and evaluate novel image reconstruction parameters for postmortem conditions, to increase image quality and diagnostic potential of CT scans. Method: Twenty PMCT scans of deceased hereof two in severe decay were subjected to four reconstruction techniques: a standard reconstruction algorithm, the detail reconstruction algorithm and two novel algorithms based on the standard algorithm, but with different Hounsfield settings. Image quality was evaluated by visual grading analysis (VGA) by four forensic radiologist observers. Results: The VGA did not prove that any of the reconstruction techniques were superior to the others. For standard and detail, the two pre-defined reconstruction algorithms, VGA scores were indiscernible and were superior to the equally indiscernible Hounsfield reconstructions on parameters translated into Sharpness and Low Contrast Resolution. The two alternative Hounsfield settings were superior with respect to Noise and Artifacts/Beam Hardening. Conclusion: The study elucidates the possiblity for multiple reconstructions specialized for PMCT conditions, to accommodate the special conditions when working with the deceased. Despite the lack of clear improvements in the tested reconstructions, this study provides an insight into some of the possibilities of improving PMCT quality using reconstruction techniques.